Legal Ambiguity in Determining PPAT Honoraria: Economic Value, Fairness, and Legal Certainty - Abdur Rahman; Heru Kuswantoi (Journal Evidence Of Law, 2026)
This study aims to construct the concept of the economic value of service fees for Land Deed Officials (PPAT) based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 33 of 2021, as well as to examine its consistency from the perspectives of legal certainty and justice. This research employs a normative juridical method, utilizing statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively through legal reasoning techniques. The findings indicate that the regulation of the economic value of PPAT service fees is normatively intended to establish a balance between public interests and the professional interests of PPAT. However, the provision still contains normative ambiguities that may lead to multiple interpretations, thereby failing to fully ensure legal certainty. Furthermore, the regulatory framework has not optimally reflected the principles of justice and efficiency within the law and economics perspective. Therefore, refinement of the regulatory norms is necessary through clearer, more systematic, and consistent formulations in order to enhance legal certainty and ensure fairness for all relevant parties.